Stationarity Evaluation of Mastercard and Visa High-Frequency Data for Pairs Trading - Ponomarenko, Daria (2022)
A plot thread of stationarity concept runs through the thesis, where the main question is how important is stationarity analysis for time series in general and in trading time series in particular. With development of technologies trades are becoming faster and intervals for data transfers are getting smaller. Nowadays, we need to deal with a high-frequency data to compete on market, and special data requires specific treatment and methodology. Pairs trading strategy is build on an idea of market inefficiencies, which can be monitored, modelled and forecasted. Profit earning is an essential goal for each investor, and accurately predicted pairs variance promises assured income. However, is it possible to frame a model with this sharp prediction ability? The main condition for this is stationarity. Stationarity guarantees trend stability in time, hence, model efficiency. In the this work we are evaluating stationarity and investigating methods how to deal with it, which models are suitable for stationary forecasting and is it even possible to predict stationarity.